In-situ investigation of single particle gasification in a defined gas flow applying TGA with optical measurements - Kuester, F.; Nikrityuk, P.; Junghanns, Marcus; Nolte, Stefan; Tuennermann, A.; Ackermann, Roland; Richter, Andreas; Guhl, S.; Meyer, B. (Fuel, 2017)
The newly developed HITECOM reactor provides the possibility of in-situ analysis of single particle reactions. It combines the capabilities of a magnetic suspension thermobalance with state of the art optical analysis. The surface temperature and carbon conversion of single particles are measured under well-defined flow conditions. The generated data enables the detailed validation of CFD single particle models. For this reactor, a special temperature resistant particle holder had to be constructed, which is able to fix various particles in direct flow during gasification. An in-situ Raman spectroscopy setup was established for quantitative gas analysis at pressures between 1 and 20 bar and temperatures up to 965 °C. Here, a pulsed Nd:YAG laser at 355 nm was used as excitation source. The Rayleigh/Raman scattering was measured perpendicular to the flow direction with a spectrograph and ICCD camera. From the recorded spectra the gas concentrations were calculated. Generally, the calculated concentrations of CO, CO2and N2match the reference values from the gas chromatograph. In the present study, single coal particles of one Central German lignite and one hard coal were analyzed and monitored during gasification. The particle diameter ranged from 1 to 3 mm. Gasification experiments with CO2were carried out under isothermal conditions at 1 bar total pressure and temperatures of 800–1200 °C. The experimental data were adjusted with models by data fitting. It was found that the Random Pore Model (RPM) matches the carbon conversion of the hard coal sample and the Shrinking Core Model (SCM) matches the carbon conversion of the lignite sample. Further analysis revealed that inhomogeneous particles affect gasification kinetics. The differences in reactivity between several particles from the hard coal are significantly larger than for the lignite particles, which is in accordance to the results of the respective ultimate and proximate analyses. Additionally, it was discovered that the difference between gas and particle temperature is negligible for low reactive feedstocks within the investigated temperature range (ΔT ⩽ 5 K at 1070 °C, hard coal), whereas there was a significant difference for reactive particles (ΔT ⩽ 40 K at 1070 °C, lignite).
CRIS-Team Scopus Importer:2023-04-20
Keywords: Gas analysis; High pressure; High temperature; In-situ Raman spectroscopy; Single particle gasification; Surface temperature